Gendered missions: Women and men in missionary discourse and practice - Schouten, Maria Johanna Christina (2017)
Review of a book focusing women active in Christian religious missionary work in Africa, Asia and Oceania in the nineteenth and early twentieth century. This theme is discussed with a view to the changing gender ideologies of middle-class Europeans at the time, the major sponsors of the missions.